Analysis of Elderly Anxiety Reviewed from Age Factors and Genders in the Social Care Home UPT PSLU Blitar Tulungagung - Kusumawati, Prima Dewi; Sutrisno, Sutrisno (STRADA : Jurnal Ilmiah Kesehatan, 2019)
The population of the elderly group in Indonesia if not handled seriously, the Increasing of age will cause problems in the health, economic, and social fields. Older people are prone to various sufferings, one of which is awareness of death; this will be an important psychological problem in the elderly. The purpose of this study was to analyze the anxiety of the elderly in terms of the age of the elderly after being given progressive muscle relaxation training at the social care home of the UPT PLSU Blitar Tulungagung.